ISSFAL statement number 7 – Omega-3 fatty acids during pregnancy to reduce preterm birth. (November 2022) - Best, K P; Gibson, R A; Makrides, M
Abstract: Globally, preterm birth is the leading cause of death in children under the age of 5 years and survivors may suffer life-long consequences. Following many years of investigation, there is strong evidence that a proportion of preterm births can be prevented by increasing maternal dietary omega-3 long chain polyunsaturated fatty acid (LCPUFA) intake during pregnancy. This Statement provides a synthesis of contemporary evidence on the role of omega-3 LCPUFA on prevention of preterm birth and is designed to provide fatty acid-specific knowledge and guidance for medical practitioners, midwives, health services, professional bodies and policy makers to consider for their contextual situations. The evidence synthesis, which underpins this statement, is based on the 2018 Cochrane systematic review with supplemental evidence from RCTs completed since that time as well as other systematic reviews. Heterogeneity between studies was explored to understand how the effect of omega-3 supplementation may vary in different population groups and by dose and type of omega-3 supplementation. Most trials were conducted in upper-middle or high-income countries and the evidence are most applicable in those settings. The evidence synthesis confirmed that omega-3 LCPUFA, particularly docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), have an important role to play in determining gestational length in singleton pregnancies. Adequate intake of omega-3 LCPUFA in early pregnancy, consistent with existing nutritional guidelines, is associated with a lower risk of preterm and early preterm births for women with singleton pregnancies. Therefore, women with adequate omega-3 intakes in early pregnancy should maintain these intakes. Women who are low in omega-3 fatty acids will benefit most from omega-3 LCPUFA supplementation to reduce their risk of early birth. In such cases supplementation with a total of about 1000 mg of DHA plus EPA is effective at reducing risk of early birth, preferably with supplementation commencing before 20 weeks' gestation.